Pengaruh Resiko Likuiditas Terhadap Profitabilitas Bank Konvensional di Indonesia - Margaretha, Farah; Aditya, Krishna (Universitas Muhammadiyah Yogyakarta, Indonesia, 2013)
The purpose of this study is to acknowledge the relationship between conventional bank’s liquidity risk towards profitability, which companies are listed in Indonesian Stock Exchange between 2008-2011. The independent variables in this study are deposits, cash reserves, liquidity gap, and non performing loan, whereas dependent variable is profitability. The sampling method being used is purposive sampling with total number of 30 banks and the data analysis method being used is linear regression. The result of the study shows that there is positive relationship between deposits and cash reserves towards profitability, and negative relationship between liquidity gap and non performing loan towards profitability. This result indicates that to achieve maximum profitability, a firm has to manage it’s cash reserves and cash flows, whereas investor has to pay attention of total asset – total liabililties ratio and NPL ratio.